The effects of corruption on earnings management - Lourenço, I. C.; Rathke, A.; Santana, V.; Branco, M. C. (XVII Encuentro AECA, 2016)
This study provides empirical evidence on the effects of corruption, as proxied by Transparency International’s Corruption Perception Index, on earnings management. It tests the hypothesis of positive association between the countries’ level of corruption and the level of earnings management using a sample of foreign firms with American Depositary Receipts (ADR) in the U.S. market. Findings indicate that corruption perception is related to higher incentives for firms to manipulate earnings in the case of emerging countries. Such results are not identified in developed countries.